ARHGEF12 influences the risk of glaucoma by increasing intraocular pressure - Springelkamp, H.; Iglesias, A. I.; Cuellar-Partida, G.; Amin, N.; Burdon, K. P.; van Leeuwen, E. M.; Gharahkhani, P.; Mishra, A.; van der Lee, S. J.; Hewitt, A. W.; Rivadeneira, F.; Viswanathan, A. C.; et al. (Human molecular genetics, 2015)
Primary open-angle glaucoma (POAG) is a blinding disease. Two important risk factors for this disease are a positive family history and elevated intraocular pressure (IOP), which is also highly heritable. Genes found to date associated with IOP and POAG are ABCA1, CAV1/CAV2, GAS7 and TMCO1. However, these genes explain only a small part of the heritability of IOP and POAG. We performed a genome-wide association study of IOP in the population-based Rotterdam Study I and Rotterdam Study II using single nucleotide polymorphisms (SNPs) imputed to 1000 Genomes. In this discovery cohort (n = 8105), we identified a new locus associated with IOP. The most significantly associated SNP was rs58073046 (β = 0.44, P-value = 1.87 × 10(-8), minor allele frequency = 0.12), within the gene ARHGEF12. Independent replication in five population-based studies (n = 7471) resulted in an effect size in the same direction that was significantly associated (β = 0.16, P-value = 0.04). The SNP was also significantly associated with POAG in two independent case-control studies [n = 1225 cases and n = 4117 controls; odds ratio (OR) = 1.53, P-value = 1.99 × 10(-8)], especially with high-tension glaucoma (OR = 1.66, P-value = 2.81 × 10(-9); for normal-tension glaucoma OR = 1.29, P-value = 4.23 × 10(-2)). ARHGEF12 plays an important role in the RhoA/RhoA kinase pathway, which has been implicated in IOP regulation. Furthermore, it binds to ABCA1 and links the ABCA1, CAV1/CAV2 and GAS7 pathway to Mendelian POAG genes (MYOC, OPTN, WDR36). In conclusion, this study identified a novel association between IOP and ARHGEF12.